Achieving legitimacy through corporate social responsibility: The case of emerging economy firms - Zheng, Q.; Luo, Yadong; Maksimov, V. (Pergamon, 2015)
To manage stakeholder CSR pressures, firms from emerging economies can employ two legitimation strategies simultaneously - compliance and strategic adaptation. Compliance is useful in responding to explicitly expressed demands for CSR, while strategic adaptation is useful when a specific form of CSR is seen as most instrumental in drawing positive responses from a particular stakeholder group. We analyze the adoption of two extreme CSR forms - philanthropy and sustainability. In a sample of 288 firms from China, we demonstrate that firms adopt both CSR forms, but emphasize philanthropy when seeking legitimacy with outsider stakeholders and sustainability with insider stakeholders.